CAPITAL STRUCTURE DETERMINANTS FROM PERSPECTIVE TAXATION ON ADVERTISING COMPANIES PRINTING MEDIA LISTED ON BEI - Cahyo Ario Bimo; Dahrani Dahrani (Proceeding International Seminar of Islamic Studies, 2022)
Capital structure is a comparison between debt and equity. Capital structure is useful for measuring the proportion of debt and equity used as a source of company funding. This study aims to examine the Debt tax shield, Non debt Tax Shield, and Effective Tax Rate on Capital Structure in Advertising Printing Media Companies listed on the Indonesia Stock Exchange. The research approach used in this research is associative. The sample used by purposive sampling is 10 companies for 2014-2019. Data analysis techniques used are descriptive statistics, multiple linear regression test panel data model, hypothesis testing (t-test and F-test) and the coefficient of determination test. The results of this study indicate that partially the size of the Debt tax shield, Non-debt tax shield has an effect on the capital structure, and Effective Tax Rate has no effect on Capital Structure. Then Debt tax shield, Non debt tax shield, and Effective tax rate simultaneously affect the Capital Structure. Thus, decision makers can use these ratios as a tool of consideration in making policies in the tax system in companies.